2012
DOI: 10.1016/j.ajhg.2012.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Exome Capture and Sequencing Identifies HEATR2 Mutation as a Cause of Primary Ciliary Dyskinesia

Abstract: Motile cilia are essential components of the mucociliary escalator and are central to respiratory-tract host defenses. Abnormalities in these evolutionarily conserved organelles cause primary ciliary dyskinesia (PCD). Despite recent strides characterizing the ciliome and sensory ciliopathies through exploration of the phenotype-genotype associations in model organisms, the genetic bases of most cases of PCD remain elusive. We identified nine related subjects with PCD from geographically dispersed Amish communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
146
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(157 citation statements)
references
References 44 publications
10
146
1
Order By: Relevance
“…Of the 164 participants in the definite PCD group with two mutations in an associated PCD gene, 128 had two loss-of-function mutations, 28 had a loss-of-function mutation with either a missense variant or an in-frame deletion fulfilling criteria for pathogenic mutations, and 8 had missense mutations on both alleles fulfilling criteria for pathogenic mutations based on the previous reports (20)(21)(22). Molecular analysis of the 26 genes was performed for 174 of the 187 participants in the other/undefined group.…”
Section: Participantsmentioning
confidence: 99%
“…Of the 164 participants in the definite PCD group with two mutations in an associated PCD gene, 128 had two loss-of-function mutations, 28 had a loss-of-function mutation with either a missense variant or an in-frame deletion fulfilling criteria for pathogenic mutations, and 8 had missense mutations on both alleles fulfilling criteria for pathogenic mutations based on the previous reports (20)(21)(22). Molecular analysis of the 26 genes was performed for 174 of the 187 participants in the other/undefined group.…”
Section: Participantsmentioning
confidence: 99%
“…For nNO validation studies at six (non-UNC) sites, PCD was confirmed by PCD-specific ciliary EM defects and, by the presence of biallelic mutations in PCD genes (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Informed consent was obtained at the University of North Carolina at Chapel Hill and collaborating institutions under the auspices of Committees on the Protection of the Rights of Human Subjects.…”
Section: Original Researchmentioning
confidence: 99%
“…PCD is a group of rare human genetic diseases characterized by recurrent infections of the respiratory system, male infertility, and frequently laterality defects, all of which are tightly linked to cilia motility abnormalities. Up to now, 19 PCD genes have been identified (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). However, combined they account for about 50% of all PCD cases, suggesting the existence of multiple additional causative genes.…”
mentioning
confidence: 99%